(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
This paper aims to investigate the structural behavior of reinforced lightweight concrete beams. Attapulgite aggregate and crushed clay brick aggregate were used as coarse lightweight aggregate to produce structural lightweight aggregate concrete with 25 Mpa and 43.6 Mpa cube compressive strength and 1805 Kg/m3 and 1977 Kg/m3 oven dry density respectively. The result of reinforced lightweight concrete beams compared with reinforced normal weight concrete beams, which have 50.5 Mpa cylinder compressive strength and 2317 Kg/m3 oven dry density. For each type of concrete two reinforced concrete beams with (1200 mm length × 180 mm height × 140 mm width), one of them tested under symmetrical two-points load STPL (a/d = 2.2) and another one tested under one-point load OPL (a/d=3.3) at 28 days. The experimental program shows that a structural lightweight aggregate concrete can be produced by using Attapulgite aggregate with 25 MPa cube compressive strength and 1805 Kg/m3 oven dry density and by using crushed clay brick aggregate with 43.6 MPa cube compressive strength and 1977 Kg/m3 oven dry density. The weight of Attapulgite aggregate concrete and crushed clay bricks aggregate concrete beam specimens were lower than normal weight aggregate concrete beams by about 20.56% and 13.65% respectively at 28 days. As for the ultimate load capacities of beam specimens, the ultimate load of Attapulgite aggregate concrete beams tested under STPL were lower than that of crushed clay bricks aggregate concrete beams and normal weight aggregate concrete beams by about 4.85% and 5% respectively. While the ultimate load capacities of reinforced Attapulgite concrete beams tested under OPL were lower than that of reinforced crushed clay bricks aggregate concrete beams and reinforced normal weight aggregate concrete beams by about 10.3% and 10.5% respectively. Finally, Attapulgite aggregate concrete and crushed clay bricks aggregate concrete showed ductility and toughness less than that of Normal weight aggregate concrete.